Finite element modelling and simulations for golf impact - Tanaka, K.; Teranishi, Y.; Ujihashi, S. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2013)
The objective of this study was to construct a finite element model of a golf ball and an impact simulation model between the ball and a club, and to devise a method for the construction of simulation models by investigating the factors affecting the behaviour of the ball during and after impact. A ball model with hyperelasticity and viscoelasticity was constructed using solid elements, and the relationship between the material properties and the ball behaviour at impact was revealed by varying several material constants of the ball model. A finite element model of a club with elasticity was created from a computer-aided design surface model of a commercially available driver. The club head and shaft were modelled using solid and shell elements, respectively. The effects of initial conditions at impact on the rebound behaviour of the ball, that is, the velocity, angle and spin rate, were investigated from impact simulations by varying the impact points of the ball and the postures of the club. Then, methods for the construction of simulation models were proposed based on these relationships. Impact experiments were also conducted to obtain the ball behaviour. The results simulated using the models, constructed by the proposed methods, closely matched the experimental results.